Exploring survival and failure on the edge of commercialisation in australian technology-based start-ups - Muhos, M.; Oloruntoba, Richard; Wagner, B.; Bask, A. (ACAD CONFERENCES LTD, 2017)
© 2018 Academic Conferences and Publishing International Limited. All rights reserved. Numerous stage models have attempted to clarify management priorities during the early stages of business growth. However, more focused and context-specific studies are needed. This study seeks to clarify the early stages of technology-intensive companies in Australia. It bridges the aforementioned gap by answering the following research questions: (1) How do the experiences of managers in technology-based start-ups relate to the assumptions of stages of growth theory in the Australian context? (2) What context-specific viewpoints should be considered when using stage frameworks in the Australian context? In this retrospective multiple case study, we devise a four-stage framework describing the early stages of technology-intensive companies through three in-depth case studies. We use the sequential incident technique and semi-structured interviews for data collection. For triangulation purposes, three perspectives were analysed in each company studied: one from company management, one from operations management and one from marketing management. This study makes a preliminary test of the applicability of the framework and analyses context-specific viewpoints. Recognising these viewpoints is necessary when using this framework in Australia. The research focus of this study is limited by the context involved, the three cases examined and the study's focus on the first phase of the framework. The applicability of the results to other contexts is therefore limited. The findings of the study may be effectively used in intermediary organisations as a framework for predicting the early stages of technology-intensive companies. Contextspecific viewpoints and their effect on the early stages of companies have not been widely investigated. This work considers and provides new insights into the growth and management of technology-intensive companies in Australian context.